Effects of Organic Nano Calcium Carbonate on Aging Resistance of Bio-Asphalt - Nianting Xiao; Yongyi Zhang; Hongbo Xia; Yu Lei; Yamin Luo (Advances in Materials Science and Engineering)
To improve the aging resistance of bioasphalt and explore the impact of organic nano calcium carbonate (CaCO3) on the aging resistance of bioasphalt, the thin-film oven test (TFOT), basic property test, rheological test, four components test, and infrared spectrum test were used to study the bioasphalt with different organic nano-CaCO3 contents. The results show that the addition of organic nano-CaCO3 increases the residual penetration, residual ductility, and residual softening point of bioasphalt. Within the range of test dosage, the greater the dosage, the more significant the effect is. With the increase of organic nano-CaCO3 content, the complex modulus aging index (GAI) of bioasphalt gradually decreases, and the colloidal instability index (IC) gradually decreases. When the content is 6%, the GAI of organic nano-CaCO3 modified bioasphalt is less than that of matrix asphalt. The nanoscale super large specific surface area of organic nano-CaCO3 has an adsorption effect on the light components in bioasphalt, which slows down the volatilization loss of light components and the oxidation process of asphalt. The addition of organic nano-CaCO3 helps to reduce the change rate of the carbonyl index and sulfoxide index.